Developing Speaking Skills of the Eighth Grade Students of SMP Negeri 1 Sigi thourgh Small Group Discussion - Farianka, Astrid; Nadrun, Nadrun; Hasyim, Zarkiani (Riwayat: Educational Journal of History and Humanities, 2025)
This research examines the impact of the Small Group Discussion (SGD) technique on improving the speaking skills of the eighth-grade students at SMP Negeri 1 Sigi, with particular emphasis on vocabulary, pronunciation, and fluency. Employing a quasi-experimental design, the study compared an experimental group taught using SGD with a control group receiving conventional instruction. Both groups completed pre-tests and post-tests to assess their progress. The data were analyzed using the Wilcoxon Signed Ranks Test, Mann-Whitney U Test, and descriptive statistics. Results showed that the experimental group experienced a significant improvement in all targeted speaking sub-skills, with average scores increasing from 15.14 to 21.14, while the control group showed only a slight improvement from 15.49 to 16.07. Statistical analysis confirmed a highly significant difference (p 0.05) between the two groups, demonstrating the greater effectiveness of SGD compared to the conventional method in enhancing speaking skills. The study concludes that SGD fosters active engagement and self-confidence, providing a positive and supportive environment for language learning. These findings offer practical insights for English language teaching, endorsing SGD as an effective strategy to boost students' communicative competence.